Teleostei, Elasmobranchii, Malacostraca, dan Cephalopoda: Potensi Sumber Daya Laut Berbasis Keanekaragaman Hayati di TPI Kabupaten Pangandaran - Meisya Fajri Wahyuni; Diana Hernawati; Rita Fitriani (Universitas PGRI Silampari, 2024)
Pangandaran Regency has a very large marine area with the potential for diverse marine biota. To determine the diversity of species in the Teleostei, Elasmobranchii, Malacostraca, and Cephalopoda classes landed at landing sites (TPI) in Pangandaran Regency, research was conducted at three stations, namely TPI Bojongsalawe, TPI Batukaras, and TPI Pangandaran. The research used descriptive quantitative methods with survey techniques, while sampling marine biota used purposive sampling techniques. There were 90 species of marine biota identified from the three stations in the Teleostei, Elasmobranchii, Malacostraca and Cephalopoda classes. The diversity index was highest at TPI Bojongsalawe with a value of 2.85. The diversity index was lowest at TPI Batukaras with a value of 0.03. The uniformity index was highest (0.68) at TPI Bojongsalawe and lowest at TPI Batukaras (0.02). The dominance index was highest (0.99) at TPI Batukaras, and lowest at TPI Bojongsalawe (0.11). The species that dominated the landings at TPI Batukaraswas Triciurus sp., so that the diversity index at TPI Batukaras was in the low category.